Ground-based remote sensing and imaging of volcanic gases and quantitative determination of multi-species emission fluxes - Platt, Ulrich; Bobrowski, Nicole; Butz, André (Geosciences, 2018)
The physical and chemical structure and the spatial evolution of volcanic plumes are of great interest since they influence the Earth’s atmospheric composition and the climate. Equally important is the monitoring of the abundance and emission patterns of volcanic gases, which gives insight into processes in the Earth’s interior that are difficult to access otherwise. Here, we review spectroscopic approaches (from ultra-violet to thermal infra-red) to determine multi-species emissions and to quantify gas fluxes. Particular attention is given to the emerging field of plume imaging and quantitative image interpretation. Here UV SO2 cameras paved the way but several other promising techniques are under study and development. We also give a brief summary of a series of initial applications of fast imaging techniques for volcanological research.
Gesehen am 14.02.2018